Strain and orientation engineering in ABO3 perovskite oxide thin films. (13th April 2022) - Sando, Daniel
Abstract: Perovskite oxides with chemical formula ABO3 are widely studied for their properties including ferroelectricity, magnetism, strongly correlated physics, optical effects, and superconductivity. A thriving research direction using such materials is through their integration as epitaxial thin films, allowing many novel and exotic effects to be discovered. The integration of the thin film on a single crystal substrate, however, can produce unique and powerful effects, and can even induce phases in the thin film that are not stable in bulk. The substrate imposed mechanical boundary conditions such as strain, crystallographic orientation, octahedral rotation patterns, and symmetry can also affect the functional properties of perovskite films. Here, the author reviews the current state of the art in epitaxial strain and orientation engineering in perovskite oxide thin films. The paper begins by introducing the effect of uniform conventional biaxial strain, and then moves to describe how the substrate crystallographic orientation can induce symmetry changes in the film materials. Various material case studies, including ferroelectrics, magnetically ordered materials, and nonlinear optical oxides are covered. The connectivity of the oxygen octahedra between film and substrate depending on the strain level as well as the crystallographic orientation is then discussed. The review concludes with open questions and suggestions worthy of the community's focus in the future.